Computed Tomographic Findings in Children with Cerebral Palsy in a Developing Country - Jahan, Roushan; Rahman, Md Mizanur; Fatema, Kanij; Karim, Md Enayet; Roy, Subrata (Journal of Enam Medical College, 2023)
Background: Cerebral palsy (CP) is one of the most common causes of chronic childhood disability. To know the aetiopathogenesis, severity and prognosis of CP, neuroimaging is an important modality of investigation. Objective: This study was done to observe the findings in CT scan of brain in children with CP. Materials and Methods: This is a cross-sectional descriptive study. One hundred and ten patients who were clinically diagnosed as cerebral palsy were enrolled in the study. After selection of the subjects, demographic and clinical characteristics were recorded. All other comorbidities including visual and hearing impairments were identified. CT scan of brain was done in all children and reporting had been done by a single qualified radiologist. Results: The mean age of the studied children was 2.6±2.2 years (1 to 14 years). Seven types of CP were found in the study group. Among them quadriplegic CP were the most common (39.1%). History of perinatal asphyxia was found in 81.8% children. Cognitive delay was found in 90% children, speech delay was found in 88.2% children, visual impairment was found in 35.5% children and hearing impairment in 31.8% cases. Epilepsy was found in 44.4% among studied subjects. Most common finding on CT scan of brain was cerebral atrophy (62.7%), followed by encephalomalacia (15.5%), calcification (13.6%), and brain malformations (11.8%). Abnormal CT scan findings were found in 88.2% of study population. Conclusion: This study showed that most common type of CP was quadriplegic CP. Maximum children had abnormal CT scan findings. Most common CT scan finding was cerebral atrophy. J Enam Med Col 2021; 11(1): 18-23